Organization of Internal Financial Control by State Customers during Planning Purchases of Goods, Works and Services - N. D. Goryunova; D. N. Gromov; A. E. Kuzmin (Управленческое консультирование)
Currently, issues related to improving the efficiency, effectiveness of procurement of goods, works, ensuring transparency and transparency in the implementation of such purchases, prevention of corruption and other abuses are resolved through the establishment of a contractual system in the field of procurement. Federal Law No. 44-FZ of 05.04.2013 “On the Contract System in the Sphere of Procurement of Goods, Works, Services for Ensuring State and Municipal Needs” (hereinafter referred to as the “Federal Law”) deals in detail with issues related to planning and procurement, as well as control compliance with the legislation of the Russian Federation and other regulatory legal acts on the contract system in the procurement sphere. At the same time, the Federal Law does not regulate relations concerning the implementation of internal financial control over the implementation of purchases.This article suggests recommendations for the organization of internal financial control of budgetary procedures related to the planning of procurement by government customers.